Shaping the Future of “Cardio-Kidney-Metabolic” Health: Insights From The Texas Heart Institute's 2024 Cardiometabolic Syndrome Conference - Arjun Raghuram; Keri Sprung, MBA; Stephanie Coulter, MD; Joseph G. Rogers, MD (Texas Heart Institute Journal)
At the Texas Heart Institute's 2024 Cardiometabolic Syndrome Conference, held on August 23, 2024, experts from diverse academic fields spoke about novel initiatives for addressing the worsening projections for cardiometabolic syndrome. Four major areas in which innovation is ongoing were highlighted: technology, policy, population health, and lifestyle and behavioral modification. This article presents a brief contextualization, summary, and analysis of the novel initiatives being implemented in each of these 4 areas to address cardiometabolic syndrome. Despite alarming projections, cardiometabolic syndrome presents a unique opportunity for innovators to drive change through collaborative, multidisciplinary efforts.